Diversity of parasitoid Lepidopterans larvae on Brassicaceae in West Sumatra (Biodiversitas Journal of Biological Diversity, 2009)
Nelly N, Rusli R, Yaherwandi, Yusmarika F (2010) Diversity of parasitoid Lepidopterans larvae on Brassicaceae. Biodiversitas 11: 93-96. Diversity of parasitoid lepidopterans larvae on Brassicaceae was conducted in several Brassicaceae areas in West Sumatra. The objective of the research was to study the diversity of parasitoid lepidopterans larvae on Brassicaceae. Sampling was conducted on Brassicaceae plants: cabbage, cauliflower, petsai and sawi. It was taken five samples in every plot, by using W method. Collection technique was done by direct collecting larvae, by using yellow trap and insect net. Adult of parasitoids was identified until family. The result of the research indicated that there was the diversity of parasitoid lepidopterans, the highest diversity was found on sawi. Thenumber of parasitoid Lepidopterans larvae found was 566, 83 species, 9 families. The degree of parasitation on the three plants was low.Key words: Brassicaceae, diversity of parasitoid, Lepidoptera.